Flood Disaster Risk Model in Karawang Regency's Industrial Area, West Java Province, Indonesia - Aruminingsih Aruminingsih; Dwi Nowo Martono; Tri Edhi Budhi Soesilo; Rudy Parluhutan Tambunan (Indonesian Journal of Geography, 2022)
Telukjambe Barat and Telukjambe Timur Sub-Districts, Karawang Regency, have a high flood risk level due to changes in Land Use/Land Cover and the yearly occurrence of runoff water discharge. This research aims to analyze the rate and pattern of land-use change due to industrial development, examine the correlation of flood impacts with environmental-socio-economic factors, and develop a flood risk model in industrial areas. Data were collected through methods of system dynamics, remote sensing, geographic information system, questionnaire distribution, focus group discussions, and in-depth interviews with stakeholders. The results showed that floods in this regency are due to massive inland changes, such as the transition from vegetation and water bodies to industrial and residential areas and a strong relationship between environmental-social-economic factors. In other cases, areas with urban land conversion are likely to be flood-prone zones in places such as the Philippines, Belgium, and China. Based on the correlation test that has been conducted, the relationship with the highest level of closeness is the correlation between environmental factors and the impact of flooding, which has a value of 0.791. Therefore, the disaster risk model with an integrated spatial plan approach and an ecological perspective is an option for realizing sustainable development in industrial areas in Karawang Regency.